Broadband white-light emission in a one-dimensional organic–inorganic hybrid cadmium chloride with face-sharing CdCl6 octahedral chains. Issue 1 (18th December 2020) - Qi, Zhikai; Chen, Yali; Guo, Yao; Yang, Xuelian; Zhang, Fu-Qiang; Zhou, Guojun; Zhang, Xian-Ming
Abstract : A new one-dimensional Cd-based hybrid halide with face-sharing CdCl6 octahedral chains exhibited a bright white-light emission upon ultraviolet photoexcitation. Abstract : One dimensional (1D) hybrid metal halides with core–shell quantum wire structures can display superior photoluminescence (PL) properties, e.g. high photoluminescence quantum yield and long lifetime; however, the single component white-light emissions in 1D hybrid systems composed of face-sharing octahedral chains have been only rarely reported. Herein, we report on a new 1D organic–inorganic hybrid cadmium chloride, (2cepiH)CdCl3 (2cepi = 1-(2-chloroethyl)piperidine), containing face-sharing CdCl6 octahedral chains. This incredible 1D Cd-based halide exhibited a bright white-light upon ultraviolet photoexcitation, which had an ultra-high color rendering index of 89 along with the CIE chromaticity coordinates of (0.27, 0.31). The fundamental mechanism of white-light emission was assigned to the synergistic emissions of free excitons and self-trapped excitons, as confirmed by the temperature-dependent PL spectra. To our knowledge, it is the first time that self-trapped exciton states are reported in 1D Cd-based hybrid materials with broadband white-light emission. Furthermore, both the experimental and the calculated results confirmed the semiconducting behavior of (2cepiH)CdCl3, and the band structure was determined by the inorganic frameworks. Our work provides a new idea to design novel single component white-light emitters.